Migration route of Fasciola into the liver. Issue 1 (9th November 2018) - Lockart, Ian; Das, Amitabha; Merrett, Neil D; Levy, Miriam T
Abstract : Humans usually acquire Fasciola infection by eating contaminated aquatic vegetation, such as watercress. After ingestion, Fasciola metacercariae excyst in the duodenum. In contrast to other liver flukes (Clonorchis and Opisthorchis) that migrate through the ampulla of Vater and ascend the biliary tree, Fasciola metacercariae penetrate the duodenal wall, migrate through the peritoneal cavity, and enter the liver. After a period of migrating randomly through the liver parenchyma, they eventually reach the larger biliary ducts and mature into adults. We present a case that illustrates this migration route of Fasciola. Abstract : After ingestion, fasciola metacercariae penetrate the duodenal wall, migrate through the peritoneal cavity and enter the liver. After a period migrating randomly through the liver parenchyma, they eventually reach the larger biliary ducts and mature into adults. We present a case that illustrates this migration route of Fasciola.